A Novel Compound Heterozygous CYP17A1 Variant Causes 17α-Hydroxylase/17, 20-Lyase Deficiency - Chen, Hong; Yuan, Ke; Zhang, Bingtao; Jia, Zexiao; Chen, Chun; Zhu, Yilin; Sun, Yaping; Zhou, Hui; Huang, Wendong; Liang, Li; Yan, Qingfeng; Wang, Chunlin (Frontiers in Genetics, 2019)
Background: Congenital adrenal hyperplasia (CAH) encompasses a group of autosomal recessive diseases characterized by enzyme deficiencies within steroid hormone anabolism which lead to disorders in cortisol synthesis. The 17α-hydroxylase/17,20-lyase deficiency (17-OHD) is an uncommon form of CAH caused by variants in the CYP17A1 gene. Aims: We report a novel compound heterozygous CYP17A1 variant and its association with the pathogenesis of 17-OHD. Methods: The patient was assessed formedical history, clinical manifestations, physical examination, laboratory examination, karyotype analysis and adrenal computed tomography. Mutation screening was conducted using whole exome sequencing (WES) and Sanger sequencing. The wild-type and mutant CYP17A1 cDNA were amplified and cloned into a pcDNA3.1(+) vector. These plasmids were transfected transiently into HEK-293T cells, respectively. Quantitative PCR and Western blotting analysis were performed to measure the expression level of P450c17. An enzymatic activity assay was conducted measuring the content of 17-hydroxyprogesterone (17-OHP) and dehydroepiandrosterones (DHEA) in medium using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: The proband was characterized by 17-OHD with rhabdomyolysis, hypokalemia and adrenal insufficiency. Novel compound heterozygous variants of the CYP17A1 gene (c.1304T>C/p.Phe435Ser and c.1228delG/p.Asp410Ilefs*9) were identified. The enzymatic activity assay revealed that this variant resulted in a complete deficiency of 17α-hydroxylase and 17,20-lyase activity. This was consistent with the hormonal characteristics of the proband’s blood. Conclusions: These results suggest that the compound heterozygous variant of c.1304T>C and c.1228delG of the CYP17A1 gene can lead to17-OHD. Our findings thus provide a novel insight into the clinical evaluations and molecular basis of 17-OHD.